“ENHANCING THE PROFESSIONAL COMPETENCIES OF PHYSICAL EDUCATION TEACHERS THROUGH DIGITAL AND INTERACTIVE APPROACHES IN HIGHER EDUCATION” - Musayev Otabek Qudratovich (NEW SCIENTIFIC PERSPECTIVES AT THE INTERSECTION OF LANGUAGE, CULTURE, AND TECHNOLOGY, 2025)
Abstract: This article investigates the enhancement of professional competencies of physical education teachers in higher education through digital and interactive approaches. It emphasizes the integration of competency-based methods, practical skills, and reflective practices to improve instructional quality. The study highlights the role of digital technologies, interactive exercises, and modern pedagogical strategies in promoting active student engagement, fostering holistic development, and supporting continuous professional growth. Recommendations for the effective implementation of these approaches in teacher training programs are also provided.